2022
DOI: 10.1515/opag-2022-0144
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Arabica coffee business in West Java, Indonesia: A multidimensional scaling approach

Abstract: Arabica coffee plantation area is limited, and production is still low while demand increases. The development of Arabica coffee in Indonesia faces many obstacles that threaten its sustainability. The objective of this study is to determine the sustainability status of the Arabica coffee business in West Java and formulate a sustainability strategy. Primary data were obtained through interviews with respondents and key persons from relevant stakeholders from upstream to downstream using a structured questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…However, the coffee shops have weaknesses in terms of their less strategic location, slow production technique, and limited promotion using only Instagram. The external analysis revealed that the coffee shops have opportunities in terms of having experienced HR and unique coffee raw materials, but they also face threats such as having a non-privately owned place of business, competition from many similar coffee businesses, and interference and security permissions (Ayse Begum et al, 2020;Azavedo & Gogatz, 2021;Berampu et al, 2019;Donovan et al, 2020;Joesyiana et al, 2021;Kaniawati et al, 2021;Lee et al, 2018;Lubis & Fitria, 2021;Prasetyo & Irma, 2021;Yusuf et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, the coffee shops have weaknesses in terms of their less strategic location, slow production technique, and limited promotion using only Instagram. The external analysis revealed that the coffee shops have opportunities in terms of having experienced HR and unique coffee raw materials, but they also face threats such as having a non-privately owned place of business, competition from many similar coffee businesses, and interference and security permissions (Ayse Begum et al, 2020;Azavedo & Gogatz, 2021;Berampu et al, 2019;Donovan et al, 2020;Joesyiana et al, 2021;Kaniawati et al, 2021;Lee et al, 2018;Lubis & Fitria, 2021;Prasetyo & Irma, 2021;Yusuf et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy assessment of goodness of fit in MDS analysis is determined by the resulting stress value. A good model is indicated by a stress value <0.25 and an R-square value or RSQ value close to 1 [16]. The multidimensional stress value was found to be less than 0.25, and the RSQ value approached 1, indicating that the model is robust and capable of accurately assessing the sustainability status of garlic development (Table 1).…”
Section: Sustainability Statusmentioning
confidence: 97%
“…Leverage analysis is a sensitivity analysis to determine variables or attributes sensitive to changes in sustainability scores [13]. The greater the leverage analysis value, the more sensitive the attribute influences sustainability [13,16]. Leverage attribute which is an attribute that needs to be improved in order to improve the index and status of each dimension.…”
Section: Leverage Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The Multi Dimension Scaling (MDS) method has been widely used to observe the sustainability of a business in Indonesia [37][38][39][40][41][42][43][44][45]. However, the MDS method is rarely used to measure the sustainability of LKMA.…”
Section: Tools Analysismentioning
confidence: 99%